Produção de blocos de concreto com adição de resíduos da construção civil e indústria química - Junkes, Valderice Herth (2023)
The growing amount of urban solid waste becomes a problem for society due to the environmental impacts related to improperly disposal. There is a demand for sustainable solutions such as recycling and reuse of waste, fulfilling the circular economy objectives and the proposed goals of sustainable development of the United Nations 2030 agenda, which deals with the production and sustainable consumption. Based on this context, the present study aimed to evaluate the quality parameters of concrete blocks, for paving, produced with the recycled waste from civil construction (concrete and gypsum) and chemical industry (tannery sludge) added. To achieve this, the materials were characterized by Xray diffraction, scanning electron microscopy, energydispersive Xray spectroscopy and granulometric analysis of the aggregates. Subsequently, aiming to evaluate the characteristics of the running blocks, tests were carried out on compressive strength, flexural traction, water absorption and leaching test. The results indicated that the paving concrete blocks produced for paving with the addition of residues in the replacement of stone dust and sand did not obtain gains in the values of mechanical resistance to compression and traction in flexion when compared to blocks made with standard raw material, however, despite the drop in resistance, they continued showing adequate results in accordance with Brazilian and international technical standards. The blocks produced with recycled concrete in the replacement of stone dust obtained satisfactory results for use in street paving after 7 days of concrete curing, reaching values between 36.54 MPa and 44.6 MPa for the mentioned properties, and reaching 28 days showed an increase of 21.4% in resistance. The blocks produced with gypsum presented values between 37.03MPa and 39.85MPa after 28 days of curing, allowing their use for street paving. On the other hand, the blocks produced with waste from the chemical industry did not obtain satisfactory results for use in street paving. Concerning the water absorption, it was noted that the blocks with the addition of civil construction waste and gypsum were promising, with values below 6% of absorption. It is also noted that the blocks produced with recycled concrete showed an improvement in performance with a waste amount of 50%, and in the economic analysis these were the blocks that presented the best costbenefits, believing that the optimal formulation is found in 55.5% replacement.